ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN AKADEMI MARITIM NUSANTARA - Andi Hendrawan; Hari Sucahyawati; Indriyani - (Universitas Muhammadiyah Semarang, 2017)
The objective of this research were to know Organizational Citizenship Behavior (OCB) at AMN employee. Organizational Citizenship Behavior (OCB) as an individual behavior that is discretionary, not directly or explicitly recognized by the formal reward system, and that in the aggregate promotes the effective functioning of the organizationThe excellent performance of demanding